2017
DOI: 10.1016/j.ijsu.2017.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative neuromonitoring in thyroid surgery: Is the two-staged thyroidectomy justified?

Abstract: Our results show that IONM has a very high sensitivity and negative predictive value, but also good specificity and positive predictive value. For these reasons, in selected patients with LOS, the surgical strategy should be reconsidered. However, patients need to be informed preoperatively about potential strategy changes during the planned bilateral surgery. Future larger and multicenter studies are needed to confirm the benefits of this therapeutic strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 27 publications
1
46
0
2
Order By: Relevance
“…Although mortality due to this surgical procedure is negligible, morbidity remains a challenging problem, even in the most experienced hands. In this kind of surgery, morbidity is mainly represented by recurrent laryngeal nerve injury, hypoparathyroidism and cervical haematoma [ 21 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although mortality due to this surgical procedure is negligible, morbidity remains a challenging problem, even in the most experienced hands. In this kind of surgery, morbidity is mainly represented by recurrent laryngeal nerve injury, hypoparathyroidism and cervical haematoma [ 21 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we demonstrated that the analysis of liquid biopsy can help in the identification of a subset of PTCs with more aggressive characteristics even in the group of low-risk cancer patients. The use of an effective method in the early identification of a thyroid tumor could permit a minimal invasive surgery preventing some of the complication related to conventional surgery [37,38]. Our data suggest the potential utility of liquid biopsy in guiding the surgical decision, however, additional studies addressing this specific question are needed.…”
Section: Discussionmentioning
confidence: 85%
“…Over the years, oncologic radicality in case of two-staged thyroidectomy has been a matter of debate; in this regard, we should consider that differentiated thyroid tumors have a good prognosis even in case of local or distant metastases, and that radioablative therapy with iodine-131 can be delayed safely. Thus twostaged thyroidectomy seems to be adequate also in case of thyroid carcinoma [38]; in this case, the endocrinologist can prescribe a TSH-suppressive therapy to reduce the risk of tumor progression of eventually unresected foci of tumor. Alternatively, a near-total lobectomy could be performed on the second side to preserve contralateral RLN.…”
Section: Two-staged Thyroidectomymentioning
confidence: 99%